Glutamate and GABA in Appetite Regulation - Delgado, Teresa C. (Frontiers in Endocrinology, 2013)
Appetite is regulated by a coordinated interplay between gut, adipose tissue and brain. A primary site for the regulation of appetite is the hypothalamus where interaction between orexigenic neurons, expressing Neuropeptide Y/Agouti-related protein, and anorexigenic neurons, expressing Pro-opiomelanocortin cocaine/Amphetamine-related transcript, controls energy homeostasis. Within the hypothalamus, several peripheral signals have been shown to modulate the activity of these neurons, including the orexigenic peptide ghrelin and the anorexigenic hormones insulin and leptin. In addition to the accumulated knowledge on neuropeptide signaling, presence and function of amino acid neurotransmitters in key hypothalamic neurons brought a new light into appetite regulation. Therefore, the principal aim of this review will be to describe the current knowledge of the role of amino acid neurotransmitters in the mechanism of neuronal activation during appetite regulation and the associated neuronal-astrocytic metabolic coupling mechanisms. Glutamate and GABA dominate synaptic transmission in the hypothalamus and administration of their receptors agonists into hypothalamic nuclei stimulates feeding. By using 13C High-Resolution Magic Angle Spinning Nuclear Magnetic Resonance spectroscopy based analysis, the Cerdán group has shown that increased neuronal firing in mice hypothalamus, as triggered by appetite during the feeding-fasting paradigm, may stimulate the use of lactate as neuronal fuel leading to increased astrocytic glucose consumption and glycolysis. Moreover, fasted mice showed increased hypothalamic [2-13C]GABA content, which may be explained by the existence of GABAergic neurons in key appetite regulation hypothalamic nuclei. Interestingly, increased [2-13C]GABA concentration in the hypothalamus of fasted animals appears to result mainly from reduction in GABA metabolizing pathways, rather than increased GABA synthesis by augmented activity of the glutamate-glutamine-G